2014
DOI: 10.15270/45-2-209
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Students, Service Delivery Organisations and Community Members of Service Delivery to a Disadvantaged Community by Social Work Students

Abstract: INTERVIEWS WITH COMMUNITY MEMBERSPROBLEM STATEMENTThis research is part of a more extensive research project in which the Departments of Social Work, Nursing and Communication collaborated to investigate the experiences of senior students' health care service delivery to a disadvantaged community, and to make recommendations to enhance quality multi-disciplinary health care service delivery to a disadvantaged community by the students of the University as part of their experiential learning.This article will f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Previous research that was conducted with social work students in Southern and East Africa suggested that students were exposed to a range of new and challenging experiences, including new contexts, concepts, work practices, terminology and discourse, ethical dilemmas, and confronting human conditions (Beytell, 2014; Ferguson and Smith, 2012; Orton, 2009; Sanford, 2007). However, some students, and even new graduates, reported being inadequately prepared for the reality or ‘culture shock’ of placement, and the application of social work theory to practice (Beytell, 2014; De Jager, 2013; Dhemba, 2012; Ferguson and Smith, 2012; Strydom et al, 2009). Combined with the findings from this study, a targeted investigation of student perceptions and experiences of preparedness, stress and vulnerability is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research that was conducted with social work students in Southern and East Africa suggested that students were exposed to a range of new and challenging experiences, including new contexts, concepts, work practices, terminology and discourse, ethical dilemmas, and confronting human conditions (Beytell, 2014; Ferguson and Smith, 2012; Orton, 2009; Sanford, 2007). However, some students, and even new graduates, reported being inadequately prepared for the reality or ‘culture shock’ of placement, and the application of social work theory to practice (Beytell, 2014; De Jager, 2013; Dhemba, 2012; Ferguson and Smith, 2012; Strydom et al, 2009). Combined with the findings from this study, a targeted investigation of student perceptions and experiences of preparedness, stress and vulnerability is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…During training sessions prior to commencing work in the communities, students were sensitised to community concerns and were made aware of issues such as attitudes, values, customs and community patterns that define particular cultures to enable them to understand and respond respectfully and effectively to needs within the community (Strydom, Greef, Wessels, Van der Walt & Schutte, 2009). Consequently community members and the students engage easily and informal evaluations indicate that the community does value the services provided by the students.…”
Section: Community Perceptions Of Social Workersmentioning
confidence: 99%